Fishing Gear Selectivity of Wire Trap to Limbat Fish (Clarias nieuhofii) in Swamp Water Rimbo Ulu, Tebo Regency, Jambi Province - Kholis, Muhammad Natsir; Syuhada, Yudha Maulana (Jurnal Perikanan dan Kelautan, 2021)
This study aims to analyze the level of selectivity of wire trap fishing gear against limbat fish (Clarias nieuhofii) in the swamp waters of Tebo Regency, Jambi Province. Data collection was carried out by catching trials using 3 units of wire traps with 30 replications, in June-August 2020. The research data were analyzed descriptively using the logistical selectivity model of the maximum likelihood method equation in the solver program from microsoft excel. The results showed that the wire traps were not selective for size but were selective for the limbat fish species (C.nieuhofii). The selectivity curve based on the logistical function shows that the probability of being caught by fish are at 22-48 mm body height, while the size of the fish that can escape has a maximum height of 34 mm or a length of 182 mm